Historical consciousness and identity stories: searching for an ethic of history'social experience (2020)
This work aims to make a reflective analysis based on three fundamental questions, the first of which is: How can a proposal of an ethical nature derive from a hermeneutic-ontological concept of historical consciousness?, in the understanding that, in a first instance, Gadamerian hermeneutical theory is concerned with the situational-ontological aspect of the subject, while on the ethical side there is no in-depth comparable theoretical development. The second question: What is to be understood by identity stories and what are their theoretical repercussions?, given that here it is stated that in these stories historical consciousness is manifested in a way that is capable of being historized. And finally, the third question is: What answer can be given to the question of what should be done from the history that one has?, which leads reflection to the field of ethics, in the sense of asking about historical consciousness from experience social in favor of a project for the future.